Sanksi Tindak Pidana Penyelundupan Pakaian Bekas Impor Dalam Pasal 102 Undang-Undang Nomor 17 Tahun 2006 Perspektif Hukum Pidana Islam - Muhammad Hilmi Aziz; Arif Faizal, Enceng; Azazy, Yusup (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the criminal sanctions for the smuggling of imported second-hand clothing as stipulated in Article 102 of Law Number 17 of 2006 on Customs, viewed from the perspective of Islamic criminal law. The research employs a normative juridical method with a statutory and comparative approach, supported by secondary data derived from legal literature, statutory regulations, and official government reports. The findings indicate that the smuggling of imported second-hand clothing constitutes an economic crime that undermines fiscal integrity, public health, and the domestic textile industry. Article 102 provides for imprisonment and fines as sanctions, reflecting the taʿzir category in Islamic law, punishments determined by the ulil amri (legitimate authority) for maintaining public order and welfare. The analysis also reveals a strong alignment between positive law and Islamic criminal principles, particularly in achieving maqaṣid al-syari‘ah objectives such as the protection of wealth (ḥifẓ al-mal), life (ḥifẓ al-nafs), and social stability. Therefore, strengthening law enforcement, border surveillance, and public awareness is essential to uphold justice and prevent recurrent smuggling practices that harm the nation’s economic and moral order.